HUBUNGAN PENGGUNAAN TAS DENGAN GANGGUAN MUSKULOSKELETAL PADA SISWA SMA BUDAYA JAKARTA - Elisa Yusrini (2022)
Background: The use of a backpack that is not suitable will cause a negative impact for its users. These negative impacts include back pain, changes in body posture and gait and injuries. Purpose: The purpose of this study was to determine the relationship between bag use and musculoskeletal disorders in high school students in Jakarta. Method: This study is a descriptive quantitative study that focuses on examining the relationship between bag use and musculoskeletal disorders with a cross sectional approach that uses a questionnaire as an instrument to collect data. The total sample in this study was 86 students. Results: The results in this study were 93% of students had musculoskeletal disorders. There is a fairly strong relationship between bag weight and musculoskeletal disorders with a p-value (0.000) less than 0.05. There is a fairly strong relationship between the length of use of the bag with musculoskeletal disorders with a p-value (0.036) less than 0.05. There is no relationship between the type of bag and musculoskeletal disorders with a p-value (0.336) greater than 0.05. Conclusion : There is a relationship between the weight of the bag and the duration of the use of the bag with musculoskeletal disorders. There is no relationship between bag type and musculoskeletal disorders.